The interplay between nutrigenomics and low-carbohydrate ketogenic diets in personalized healthcare - Almoghrabi, Yousef M.; Eldakhakhny, Basmah M.; Bima, Abdulhadi I.; Sakr, Hussein; Ajabnoor, Ghada M. A.; Gad, Hoda M.; Mohammad, Fatma Azzahraa H.; Elsamanoudy, Salma A.; Awan, Akram Z.; Elsamanoudy, Ayman Z. (Frontiers in Nutrition, 2025)
The field of nutrigenomics explores the interaction between diet and gene expression, examining how nutrients function as signaling molecules that influence cellular processes, protein synthesis, and metabolite production. This discipline aims to design diets that promote genomic stability through various genetic mechanisms, including minimizing DNA damage and epigenetic modifications, among others. Nutrigenomic profiling helps identify individual dietary needs and responses to food interventions. Nutrigenetics, a subfield of nutritional genomics, investigates how genetic variations affect nutrient metabolism and health outcomes. It operates on the principle that genetic differences influence nutrient absorption and metabolism, shaping disease susceptibility and treatment responses. Therefore, integrating nutrigenetics into dietary planning enables the development of personalized nutrition strategies to improve health and prevent disease. One key application of nutrigenomics is its impact on various diets, including the Low-Carbohydrate ketogenic diet (LCKD), a high-fat, low-carbohydrate regimen that induces ketosis. In this metabolic state, ketone bodies serve as energy sources and signaling molecules. Research suggests that LCKD may influence gene expression and epigenetic mechanisms, modulating inflammation-related pathways, oxidative stress, and metabolic regulation. Additionally, KD has been associated with improved insulin sensitivity, glucose control, lipid profiles, and weight loss. However, genetic factors affecting LCKD response require further investigation to refine personalized dietary recommendations. This review highlights the significance of nutrigenomics, focusing on the interplay between the LCKD and genetic factors. A comprehensive understanding of these interactions is essential for developing personalized dietary strategies that optimize LCKD benefits while mitigating potential risks, ultimately contributing to individualized nutritional guidance within a precision health framework.